The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/rcm.6475
|View full text |Cite
|
Sign up to set email alerts
|

Use of modified Doehlert‐type experimental design in optimization of a hybrid electrospray ionization ion trap time‐of‐flight mass spectrometry technique for glutathione determination

Abstract: The results highlighted the possibilities offered by the employment of multifactorial optimization towards the improvement of performance of tandem mass spectrometry techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
(60 reference statements)
0
5
0
Order By: Relevance
“…However, adjustments of critical MS parameters, such as voltage and temperature, are needed to ensure stable spray and prevent gas-phase fragmentation of glycans as they travel from the emitter, through the S-lens, and into the quadrupole. Although the magnitude of these effects are instrument specific, previous work on mass spectrometer peptide optimization has indicated that the basic relationships behind these parameters are to some extent universal. , Despite evidence that design of experiments can lead to improvements in protein abundance, to date, there has been no parallel investigation of MS parameters for glycans.…”
Section: Resultsmentioning
confidence: 99%
“…However, adjustments of critical MS parameters, such as voltage and temperature, are needed to ensure stable spray and prevent gas-phase fragmentation of glycans as they travel from the emitter, through the S-lens, and into the quadrupole. Although the magnitude of these effects are instrument specific, previous work on mass spectrometer peptide optimization has indicated that the basic relationships behind these parameters are to some extent universal. , Despite evidence that design of experiments can lead to improvements in protein abundance, to date, there has been no parallel investigation of MS parameters for glycans.…”
Section: Resultsmentioning
confidence: 99%
“…GSH is one of the most abundant intracellular antioxidants in animal cells. Since it is considered to be one of the most abundant tripeptides in human organism, and its action against xenobiotics and oxidative radicals is well known (Zachariadis and Rosenberg, 2013). In mice, exposure to TCDD results in significant depletion of GSH by oxidative stress in liver (Slezak et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The methods of detecting biothiols include high performance liquid chromatography (HPLC) [23, 24], ultraviolet visible spectrometry [25, 26], electrochemical method [27, 28], capillary electrophoresis [29], mass spectrometry [30], and so forth. Among them, fluorescence method has attracted much attention due to its high sensitivity and efficiency [3138]; in particular it can be used for real-time imaging of living tissues by means of confocal detection [3941].…”
Section: Introductionmentioning
confidence: 99%